Optimalisasi Guru Dalam Pembentukan Karakter Siswa Sekolah Dasar Pada Mata Pelajaran Pendidikan Pancasila di SDN Cijoho. - Salsha Amelia; Lousy Loustiawaty (Universitas Sebelas Maret, 2025)
The purpose of this study was to determine the optimization of teachers in shaping the character of grade III A students of SDN Cijoho in the subject of pendidikan pancasila , and to determine the obstacles teachers face in shaping the character of grade III A students of SDN Cijoho in the subject of pendidikan pancasila . This study used a qualitative method with 1 homeroom teacher and 10 students as subjects, and used data analysis techniques, namely data reduction, data presentation, and conclusions. The results of the study were obtained through observation, interviews, and documentation. Observations were carried out by conducting direct observations at the research site regarding the optimization of teachers in shaping the character of elementary school students in the subject of pendidikan pancasila by the way teachers teach pendidikan pancasila using appropriate learning strategies, and also by implementing positive activities at school such as flag ceremonies, congregational dhuha prayers and morning exercises so that students' bad characters slowly begin to disappear. The obstacles faced by teachers in shaping the character of elementary school students are, limited time in educating students, differences in education between the school environment and the home, and the lack of concern from parents and the community for character education. Apart from that, there are several factors that can influence character formation in students, namely social media, the surrounding environment, lack of self-awareness in students in applying character values, and teachers who do not provide enough character education to students.